2017
DOI: 10.1016/j.advwatres.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Dual integral porosity shallow water model for urban flood modelling

Abstract: International audienceWith CPU times 2 to 3 orders of magnitude smaller than classical shallow water-based models , the shallow water equations with porosity are a promising tool for large-scale modelling of urban floods. In this paper, a new model formulation called the Dual Integral Porosity (DIP) model is presented and examined analytically and computationally with a series of benchmark tests. The DIP model is established from an integral mass and momentum balance whereby both porosity and flow variables ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
146
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(149 citation statements)
references
References 32 publications
2
146
1
Order By: Relevance
“…A large number of studies have shown that the selected indices are positively related to flood evaluation. Therefore, all indices are used in Equation (2) to normalize x ij to X ij .…”
Section: Projection Pursuit Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that the selected indices are positively related to flood evaluation. Therefore, all indices are used in Equation (2) to normalize x ij to X ij .…”
Section: Projection Pursuit Methodsmentioning
confidence: 99%
“…Along with significant changes in global climate and the considerably increasing disturbance caused by human activities, flood disasters in urban areas have become more serious, substantially restricting social and economic development and posing a threat to the safety of human lives and properties [1,2]. In recent years, urban flooding has caused many casualties and property losses in Japan, Singapore, The Netherlands, Britain and other countries [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In [14], the concept of closure is introduced. It stems from the consideration that the dual nature of the porosity (storage vs. porosity) should result in a dual denition of the ow variables (domain-based vs. boundary-based).…”
Section: Introductionmentioning
confidence: 99%
“…The IP model can be obtained as a particular case of the DIP formalism, by assuming a very specic closure. The IP closure yields inaccurate mass and momentum uxes [14]. Correcting this with the DIP closure and introducing a transient momentum dissipation model derived from [11] results in substantially improved model performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation